Household responses to poverty and vulnerability. Vol. 2, Confronting crisis in Angyalfold, Budapest, Hungary - Moser, Caroline O. N., 1944- 1944- (The World Bank, 1997)
This research paper describes the main results from the community of Angyalfold, in Budapest, Hungary. The research is concerned with the strategies adopted by the urban poor to reduce vulnerability and prevent impoverishment during periods of economic stress. This type of study assists policymakers in designing effective locally based solutions that ensure the poor are themselves active agents of growth, rather than passive recipients of compensatory measures. Three features distinguish this study from other poverty studies:a micro-level approach combining households and communities as the main units of analysis, an unusually long period of observation for some communities and households, and a comparative framework offering fours cases with very different economic development levels and institutional contexts. The study concludes with some priority recommendations for action:1) support households in their role as safety net; 2) alleviate constraints on women's labor supply; 3) ensure that social capital is not taken for granted; 4) develop social policy that integrates human capital and social capital; 5) pursue further research; and 6) develop tools and indicators to strengthen the assets of the poor